Bread Yeast Fermentation Method Production of Papaya (Carica Papaya L.) Fruit Bioethanol - I Nengah Muliarta; Ni Luh Putu Putri Setianingsih; I Wayan Sudiarta; Desak Ayu Diah Prawerti; I Kadek Somariana; I Ketut Suwarmadi Putra (East Asian Journal of Multidisciplinary Research, 2023)
Making bioethanol from papaya fruit is done through a fermentation process. Yield is influenced by the duration of fermentation and the mass variation of the bread yeast Saccharomyces cerevisiae. The pH treatment and initial sugar content of the substrate were also tested before the addition of glucose. This study aims to examine the effect of yeast concentration and fermentation time on the amount of bioethanol produced from papaya fruit in the manufacture of bioethanol. The maximum concentration of bioethanol produced by a concentration of 2% S. cerevisiae is 5.44% due to the addition of yeast, according to the number of nutrients in the sample. In order of concentration from high to low, it is 2% > 4% > 3% > 5% > 1%. While the maximum pH value of 4.9 with a concentration of 2% was obtained in ethanol production by Saccharomyces cerevisiae.